2011
DOI: 10.1080/01690965.2010.486209
|View full text |Cite
|
Sign up to set email alerts
|

On-line interpretation of intonational meaning in L2

Abstract: Despite their relatedness, Dutch and German differ in the interpretation of a particular intonation contour, the hat pattern. In the literature, this contour has been described as neutral for Dutch, and as contrastive for German. A recent study supports the idea that Dutch listeners interpret this contour neutrally, compared to the contrastive interpretation of a lexically identical utterance realised with a double peak pattern. In particular, this study showed shorter lexical decision latencies to visual targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 35 publications
1
34
1
Order By: Relevance
“…While the current data showed that even moderate-proficiency L1-Korean learners of English evoked a contrast set in response to font emphasis in written discourse, the ability to process contrastive accents in L2 speech appears modulated by L2 proficiency (e.g., Baker, 2010;Braun & Tagliapietra, 2011;Lee & Fraundorf, 2017). For instance, only high-proficiency L2 learners showed memory benefits of an L + H* pitch accent in L2 speech (Lee & Fraundorf, 2017).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…While the current data showed that even moderate-proficiency L1-Korean learners of English evoked a contrast set in response to font emphasis in written discourse, the ability to process contrastive accents in L2 speech appears modulated by L2 proficiency (e.g., Baker, 2010;Braun & Tagliapietra, 2011;Lee & Fraundorf, 2017). For instance, only high-proficiency L2 learners showed memory benefits of an L + H* pitch accent in L2 speech (Lee & Fraundorf, 2017).…”
Section: Discussioncontrasting
confidence: 62%
“…One possibility is that L2 learners show non-native processing of pitch accents because they fail to acquire the mapping between a specific pitch accent type in their L2 and its discourse function. This could well explain the Braun and Tagliapietra (2011) results, in which L1-German learners of Dutch appeared to inappropriately transfer their L1 prosodic knowledge. Similarly, it is possible that the absence of pitch accenting as a focus-marking device in Seoul Korean, which marks contrastive focus prosodically by placing an accentual phrase boundary before a focused word and dephrasing words following it (Jun, 1993(Jun, , 2005Ladd, 2008), may have prevented the L1-Korean learners of English in Lee and Fraundorf (2017) from grasping the discourse function of contrastive pitch accents in L2 speech.…”
Section: Explaining L1-l2 Differences In Discourse Processingmentioning
confidence: 72%
See 1 more Smart Citation
“…On this account, the L+H * accent should facilitate L2 listeners' rejections of all of the incorrect statements, all of which are inconsistent with the correct information. However, given the previous finding that L2 listeners can establish a contrast set upon hearing a contrastive accent (Braun & Tagliapietra, 2011), this mechanism seems to be unlikely to underlie any potential effects of contrastive accents on L2 listeners' memory for discourse.…”
Section: Present Studymentioning
confidence: 95%
“…For example, while English signals a focused word by placing a pitch accent on that word, Seoul Korean lacks pitch accents and instead conveys the same information by placing a prosodic phrase boundary before the word (Jun, 1993(Jun, , 2005Ladd, 2008). And even in other languages that use pitch accents to mark focus, such as Dutch and German, the specific prosodic contours associated with focus may differ across languages (Braun, 2006;Braun & Tagliapietra, 2011;Cohen & 't Hart, 1967;'t Hart, Collier & Cohen, 1990). Nevertheless, because pitch accents convey useful information about the information structure of an utterance (as demonstrated by their benefits for native listeners; e.g., Dahan et al, 2002;Fraundorf et al, 2010Fraundorf et al, , 2012Ito & Speer, 2006;Watson et al, 2008), it would be valuable for L2 learners to learn to process them in spite of these challenges.…”
Section: Introductionmentioning
confidence: 99%